Communicable: Source Credibility in Countering the Disruption of Healthcare Norms in New York’s Isolated Orthodox Jewish Enclaves. - Sarapin, Susan; Morris, Pamela L. (Journal of Communication & Religion)
Haredi Orthodox Jewish neighborhoods of New York have been aggressively targeted by anti-vax groups. Reaching the Haredim with misinformation is facilitated by the very accommodations used to keep the lifestyle separate and incorruptible. Actually, most rabbis, the experts on Jewish law, advocate for vaccination, and this comes straight from the communication of scripture. Despite the fact that the principles of a fundamentalist religion can complicate some life decisions, an understanding of religious law and a rabbi’s interpretation of scripture as the ultimate authoritative sources may best counter medical misinformation, both for the group itself and the public’s impressions of them.